2017
DOI: 10.18632/oncotarget.19695
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin protects against nucleus pulposus degeneration through inhibition of NF-κB signaling pathway and activation of Akt signaling pathway

Abstract: The objective of the present study was to examine the potential role of ghrelin in degeneration of nucleus pulposus (NP). Lower expression levels of ghrelin were found in human NP cells stimulated with interleukin-1β (IL-1β). Moreover, exogenous ghrelin suppressed IL-1β induced degeneration and inflammation associated biomarkers in human NP cells, including matrix metalloproteinase-13, a disintegrin and metalloproteinase with thrombospondin motifs-5, tumor necrosis factor-α and iNOS, which was possibly mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 59 publications
0
27
0
1
Order By: Relevance
“…It has been reported that ghrelin can affect many inflammatory diseases 31,32,46 , but it remains unknown whether ghrelin expression is associated with the development of contact dermatitis and psoriasis. In this study, we established mouse models of contact dermatitis and psoriasis using OXA and IMQ, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ghrelin can affect many inflammatory diseases 31,32,46 , but it remains unknown whether ghrelin expression is associated with the development of contact dermatitis and psoriasis. In this study, we established mouse models of contact dermatitis and psoriasis using OXA and IMQ, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA was extracted from the from knee joint articular cartilage or cultured primary chondrocytes of each experimental group using the RNeasy kit (Qiagen, Valencia, CA, USA) as previously reported [81], and first-strand cDNA was generated using the ImProm-II reverse transcription system (Qiagen, Valencia, CA). Real-time PCR was performed, with SYBR Green I dye used to monitor DNA synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Insulin resistance, diabetes & obesity [11][12][13], rheumatoid arthritis [70], psoriasis [95], SLE [87], atherosclerosis [147] Systemic sclerosis with PAH [82], increased appetite [126] PAI- Alzheimer's [120] Insulin resistance &diabetes [11,12], hyperlipidemia [25], kidney failure [27,28], gestational diabetes [40], IVDD [48], rheumatoid arthritis& osteoarthritis [47,58], systemic sclerosis complications: PAH, DVT, PE, digital ulcers [76,77], SLE with renal involvement [87], psoriasis [92], Alzheimer's [118], major depression & bipolar [122,123], NAFLD&NASH [125], diabetic microvascular complications [154], atherosclerosis and cardiovascular disease [155], sepsis [162], acute pancreatitis [163]…”
Section: • Preeclampsiamentioning
confidence: 99%
“…Shi et al reported increased levels of visfatin in nucleus pulposus tissue in more severe IVDD grades than less severe grades [46]. Finally, ghrelin similarly is proved to have a role in nuclear pulposus degeneration [47]. Another study by Li and colleagues showed that resistin binds to toll-like receptor 4 (TLR4) that leads to an increase in chemokine ligands 4 (CCL4) expression in nucleus pulposus cells, causing macrophage infiltration [48].…”
Section: Adipocytokines and Rheumatologymentioning
confidence: 99%